Species characteristics of childbirth chigger mites five genus in the Ala-Archa gorge of the Kyrgyz ridge (Experimental biology, 2015)
This work contains the results of years of research childbirth chigger mites (Acariformes: Trombiculidae, Leeuwenhoekiidae) of the Ala-Archa Kyrgyz ridge (Northern Tien Shan). Ticks collected in 13 areas from of the Ala-Archa gorge. Small mammals, 5 species identified parasitizing 10 species of mites of the genera Shunsennia, Leptotrombidium, Montivagum, Aboriginesia and Euschoengastia. Found that the most often on vertebrate animals parasitized E. alpinа, A. armata and L. wolandi. The intensity of the infection is registered by the dominant species of the E. alpinа - 14,6 copies and A. armata – 11,7 copies. Dominant genera was Leptotrombidium (4 species) and Aboriginesia (3 species), which ultimately amounted to 70.0% of that of the species under consideration childbirth.
Keywords: chigger mites; systematics; family; genus; species